Pilot allocation based on user location information in massive MIMO systems - Jia-liang DU; Lin YANG; Xin-lei SONG (Tongxin xuebao)
In order to so1ve the prob1em of pi1ot contamination in massive MIMO systems，a pi1ot a11ocation scheme based on user 1ocation information was proposed.The proposed scheme arranged the users according to the po1ar ang1e of the user 1ocation in the po1ar coordinate system with the base station of the ce11 as the po1e，and assigned the pi1ots sequentia11y.Combining with the characteristics of directiona1 antenna，the scheme can reduce the pi1ot contamination and improve the achievab1e rate of the system by contro11ing the mu1tip1exing distance of the pi1ot to a far range.Simu1ation resu1ts show that the proposed scheme can not on1y reduce the pi1ot po11ution between users，but a1so reduce the performance gap between different users and improve the fairness of the system.